Analysis of Road Surface Defects Using Road Condition Index Method on the Caruban-Ngawi Road Segment - A. Suraji; A. T. Sudjianto; Riman Riman (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2018)
Road maintenance action program must begin with identification of road surface defects before compiling a work program. One method of identification of road defects is the Road Condition Index (RCI) method. This method is simpler than the other methods because the survey method is by visualizing. This study aims to identify road defects with the RCI method carried out by several surveyors and how defects occur on the Caruban-Ngawi road section.The method used in this study is by direct survey of primary data on road surface defects conditions. There were 3 surveyors who conducted a survey with normal and opposite directions along the road. Data slices are made at lengths of every 100 m to identify road defects. The data is processed by doing an average on each data which is then made a strip map of road defects image. Data processing was done by determining the percentage of defects categories ranging from good, moderate, light defects, and heavy defects.The results of the study showed that the survey conducted by several surveyors was good and the general results were not significantly different. This means that the surveyors have almost the same perception in terms of assessing the condition of road defectss with the RCI method. The condition of road pavement on the Caruban-Ngawi road in general can be said that the road is still in good condition where heavy defects road damage in the normal and opposite directions is only 1.13% and 0.28% respectively.